Sistem Informasi Sarana dan Prasarana Sekolah Berbasis Website di MTs Darul Ikhlas Sangatta Selatan - Eva Nurjannah; Muhammad Ibnu Faruk Fauzi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
MTs Darul Ikhlash is one of the educational institutions in South Sangatta which is equipped with various school facilities and infrastructure. Some of the data management processes for facilities and infrastructure at MTs Darul Ikhlash still run manually and some are in the form of files, but there is no system that accommodates the facilities and infrastructure processes as a whole. So it is difficult for the deputy head of facilities and infrastructure to find out and search for data held by the school, as well as control the inventory of facilities and infrastructure, especially those in condition that can be replaced for further improvement. The aim of this research is to design and build a website-based information system for facilities and infrastructure that is used to simplify the process of collecting data on facilities and infrastructure at MTs Darul Ikhlash so that management becomes more effective and efficient. This information system planning was created using the waterfall method. This research has produced a web-based Facilities and Infrastructure Information System for Data Collection and Loans at MTs Darul Ikhlash, which will make it easier for the school to recapitulate facility and infrastructure inventory data more quickly and accurately.